Evaluasi Kritis Kinerja IMF dalam Krisis Asia - Widarjono, Agus (Unisia, 2016)
The IMF established after World War II is a part of world society's effort to save the world from economic depression. Initially it had well-defined purposes. With the collapse of fixed exchange rate system in 1971, the IMF lost its original purposes. The institution then brings free market ideology. Fiscal Austerity, privatization and market liberalization are the three pillars of Washington Consensus advice to help countries facing economic problem. Washington Consensus, however, was designed originally to respond economic problem in Latin America where those countries have huge deficit and loose monetary policy. It is not surprise that these recipes cannot run well in the case of the East Asia Crisis. Indeed, the IMF's advice worsened the economic crisis of the regions and spread to other regions